2020
DOI: 10.1145/3419986
|View full text |Cite
|
Sign up to set email alerts
|

A Fitts’ Law Evaluation of Visuo-haptic Fidelity and Sensory Mismatch on User Performance in a Near-field Disc Transfer Task in Virtual Reality

Abstract: The trade-off between speed and accuracy in precision tasks is important to evaluate during user interaction with input devices. When different sensory cues are added or altered in such interactions, those cues have an effect on this trade-off, and thus, they affect overall user performance. For instance, adding cues like haptic feedback and stereoscopic viewing will result in more realistic user interaction, thus improving performance in these tasks. Also, adding a noticeable disparity between physical and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Selection and Reaction time was found to be substantially slower in visuo-vibrotactile feedback condition. These findings are in agreement with the findings in the study of Bricker et al, [12], where the visuohaptic condition showed significantly slower selection times on a Fitts's law task in VR. Also, our findings align with the observation of Ariza et al, [5], where the vibrotactile showed longer correction phases on Fitts's law task in VR.…”
Section: Performancesupporting
confidence: 93%
See 1 more Smart Citation
“…Selection and Reaction time was found to be substantially slower in visuo-vibrotactile feedback condition. These findings are in agreement with the findings in the study of Bricker et al, [12], where the visuohaptic condition showed significantly slower selection times on a Fitts's law task in VR. Also, our findings align with the observation of Ariza et al, [5], where the vibrotactile showed longer correction phases on Fitts's law task in VR.…”
Section: Performancesupporting
confidence: 93%
“…However, this study did not provide visual feedback to facilitate comparison against vibrotactile, and it was in normal screen display (non-VR). In contrast, using a Fitts's law task in VR (stereoscopic display), the visual feedback facilitated a substantial better selection time than the visuo-vibrotactile condition [12]. The study that seems more proximal to ours, is the study of Ariza et al, [5].…”
Section: Performance and Vibrotactile Feedback In Vrmentioning
confidence: 61%
“…Specifically, we experimented with the Google AR Core 13 , Vuforia 14 , and SolAR 15 frameworks. The marker-tracking system in AR Core was intended for use with markers placed on walls or the floor, and larger in size that can fit on a smartphone screen.…”
Section: Used Libraries and Implementation Challengesmentioning
confidence: 99%